The Civil War. The story and the artillery - Lusitana, Donna E.; Lihani, Rob.; Greystone Communications; Arts and Entertainment Network; History Channel Club. ([S.l.] : History Channel Club, 2004)
Why the war started and how it was fought. Explores one of the factors that finally helped bring it all to a close : the revolutionary new artillery weapons of the day.
DVD format.
"American history DVD archives."
Includes bonus segment, Reporting the war.
Produced by Rob Lihani ; director, Donna E. Lusitana.
Keywords: United States -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865 -- Artillery operations; United States. -- Army -- Ordnance and ordnance stores; Artillery -- History